Skyline queries for multi-criteria decision support systems - Gudala, Satyaveer Goud (Kansas State University, 2011)
In decision-making applications, the Skyline query is used to find a set of non-dominated data points (called Skyline points) in a multi-dimensional dataset. A data point dominates another data point if it is at least as good as the other data point in all dimensions and better in at least one dimension. The skyline consists of data points not dominated by any other data point. Computing the skyline points of a dataset is essential for applications that involve multi-criteria decision making. Skyline queries filter out the interesting tuples from a potentially large dataset. No matter how we weigh our preferences along the attributes, only those tuples which score best under a monotone scoring function are part of the skyline. In other words, the skyline does not contain tuples which are nobody's favorite. With a growing number of real-world applications involving multi-criteria decision making over multiple dimensions, skyline queries can be used to answer those problems accurately and efficiently. This report mainly focuses on various skyline computing algorithms which can be used for online processing efficiently and are suitable to present multi-criteria decision making scenario. I implemented the Branch-and-Bound skyline Algorithm on two different data sets; one is a synthetic dataset and the other is a real dataset. My aim is to explore various subspaces of a given dataset and compute skylines over them, especially those subspace skylines which contain the least number of the skyline points.
Keywords: Skyline queries; Computer Science (0984)